2014
DOI: 10.1093/gerona/glu024
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Risk and Body Mass Index Predict Hospitalization, Nursing Home Admissions, and Mortality in Community-Dwelling Older Adults: Results From the UAB Study of Aging With 8.5 Years of Follow-Up

Abstract: Nutritional risk was associated with all-cause hospitalizations, nonsurgical hospitalizations, and mortality. Nutritional risk may affect the disablement process that leads to health services utilization and death. These findings point to the need for more attention on nutritional assessment, interventions, and services for community-dwelling older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 30 publications
(35 reference statements)
4
42
2
Order By: Relevance
“…Suboptimal nutrition contributes to the disablement process of older adults, wherein they become progressively more frail and dependent upon health care resources, leading to increased hospital and nursing home admissions as well as increased emergency department use [89, 100]. While some contributory causes of malnutrition in older adults are immutable, many others are amenable to change.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Suboptimal nutrition contributes to the disablement process of older adults, wherein they become progressively more frail and dependent upon health care resources, leading to increased hospital and nursing home admissions as well as increased emergency department use [89, 100]. While some contributory causes of malnutrition in older adults are immutable, many others are amenable to change.…”
Section: Resultsmentioning
confidence: 99%
“…appropriate body weight and caloric intake targets). In fact, being obese increases the likelihood of institutionalization, although it can also be a reason for admission refusal by LTC facilities lacking the infrastructure to provide proper care for obese residents [8789]. …”
Section: Threats To Nutritional Status In Long Term Care Settingsmentioning
confidence: 99%
“…Obesity or mere overweight has already been shown to be associated with undesired events like hospitalization, nursing home admission, and mortality in older adults. 32 Maybe because an excessive body weight limits ADLs performance 33 and is associated with health conditions. 34 In the present study, exceeding 26.7 kg/m 2 was shown to lead to nursing home admission, particularly over 80 years of age.…”
Section: Rejuvenation Researchmentioning
confidence: 99%
“…34 In the present study, exceeding 26.7 kg/m 2 was shown to lead to nursing home admission, particularly over 80 years of age. This value, which is classified as overweight, 32 corresponded to the 50 th percentile for the population studied and was computed for both men and women. Other research 33 identified the BMI range from 22.5 to 25 kg/m 2 as the optimal range for successful and healthy aging, preventing disability and decreasing the risk of premature mortality.…”
Section: Rejuvenation Researchmentioning
confidence: 99%
“…Some of the demonstrated outcomes of under-nutrition in older individuals include poorer functional status [3], greater health services utilization, and higher likelihood of mortality [4]. Combatting under-nutrition is difficult because gaining access to sufficient and healthy foods can be particularly challenging for this population [5].…”
mentioning
confidence: 99%